Workplace violence among healthcare workers in the emergency departments in Malaysia - Mohammad Nafis Sahiran; Halimatus Sakdiah Minhat; Suhainizam Muhamad Saliluddin (Journal of Health Research, 2022)
Purpose – This study was conducted to determine the percentage and associated factors of workplace violence (WPV) among healthcare workers (HCW) working in the Emergency Departments (ED). Design/methodology/approach – A cross-sectional study was conducted among 231 HCW using proportionate stratified random sampling. A validated and reliable self-administered questionnaire was distributed among respondents who fulfilled the eligibility criteria. Only Malaysians with a minimum employment of six months in the ED were included. The data was analysed through Multiple Logistic Regression using International Business Machines Statistical Package for Social Sciences software version 24 to determine the association between the independent variables and WPV. Significance level was set at 0.05 (p = 0.05) at 95% confidence interval (CI). Findings – The percentage of WPV was 38%, of which 88.9% were psychological violence and were mostly perpetrated by combinations of perpetrator types (51.9%). Those aged 40 years and below, with low job support, and working in a secondary hospital have 5.4 (AOR = 5.366, 95% CI: 1.51–19.05), 2.9 (AOR = 2.871, 95% CI: 1.44–5.73) and 2.7 (AOR = 2.737, 95% CI: 1.50–5.01) times higher odds, respectively, of experiencing WPV. Originality/value – The findings revealed a relatively high percentage of WPV among the HCW working at the ED with those of younger age with low job support and working in secondary hospitals being more at risk. Early interventions to reduce WPV are necessary in targeting those with identified risks.